The Prophetic Approach to Building and Raising People Religiously and Morally During the Meccan Period - Youssf ben Muhammed Amehdi (LECTURES: Journal of Islamic and Education Studies, 2024)
The events and turning points of the Prophet’s biography constituted, and still are, a source for providing the contemporary Muslim mind, and a source for understanding global events and the map of societies, through awareness of their events and awareness of their important lessons. The unique personality of Muhammad, may God’s prayers and peace be upon him, cannot be measured only by the achievements that took place during his time, but also by what resulted from them and what was achieved after him. He built a new, unified nation after dispersal, and produced great leaders from it, and made the Muslim person a civilized example with his mind. His approach, may God bless him and grant him peace, was purification, education, changing souls, refining them, and building hearts, based on firm and solid divine foundations to liberate man from slavery to other than God, correct his faith, purify himself with various types of worship and obedience, and refine him with good morals. By raising his companions, may God be pleased with them, the Prophet, may God bless him and grant him peace, achieved this eternal model of the righteous, divine human being. Accordingly, this paper aims to highlight the components of devotional and moral construction through applied models from the Meccan era, and to explain the methods that the Prophet, may God bless him and grant him peace, followed to achieve this, and the effects resulting from it, and to establish that following the example of our Master Muhammad, may God bless him and grant him peace in general, and his educational and moral curriculum in particular. A legal requirement and a religious necessity. Hence, the following questions can be asked: How was the Prophet, may God bless him and grant him peace, able to build the personality of a Muslim during the Meccan era, religiously and morally? What are the methods and components that were relied upon to achieve this balanced structure religiously and morally? How can the prophetic model be invested in improving our moral system? To address this topic, we have divided it into three sections: The first topic: The components of devotional construction during the Meccan era, The second topic: The elements of moral construction during the Meccan era, The third topic: The fruits and effects of the Prophet’s method in the devotional and moral structure during the Meccan era.